On-line therapeutic group: care device for the mental health of college students in pandemic times - Vivenzio, Rafaella Andrade; Amorim, Ana Elisa Reis; Sousa, Johnatan Martins; Farinha, Marciana Gonçalves (Revista de Psicologia, 2022)
The COVID-19 pandemic caused changes in the geopolitical and cultural pillars of society, which may result in negative psychological impacts in the face of the uncertainties of the scenario. Young university students, often identified as a population vulnerable to the development of anxiety, depression and stress, demand qualified care from mental health devices, in order to welcome suffering and develop coping strategies in the face of health emergencies. Therefore, the objective was to report the experience of a brief group intervention, in order to reflect on the importance of online therapeutic groups structured in a transdisciplinary way. These are considered to be powerful psychosocial care tools and can be included in programs to prevent and remediate the damage caused by the COVID-19 pandemic. Therapeutic groups proved to be potential tools for coping with the impacts caused by the health emergency scenario and welcoming the emotional demands of the academic community, contributing to a better quality of life for university students.